PENERAPAN BLENDED LEARNING UNTUK MEMBENTUK MODEL MENTAL SISWA KELAS XI IPA SMA PGRI 4 BANJARMASIN PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN - Merry Setiawati; Arif Sholahuddin (Universitas Lambung Mangkurat, 2015)
Abstract. A research on the application of blended learning in the material solubility and solubility product. This study aims to determine (1) the formation of students' mental models after using blended learning, (2) the difference between the results of student learning through the implementation of blended learning and conventional learning material is applied to the solubility and solubility product of high school students of class XI Science PGRI 4 Banjarmasin, (3) students' response to the application of blended learning and conventional learning material that is applied to the solubility and solubility product of high school students of class XI Science PGRI 4 Banjarmasin. The research method used was a quasi experiment. Research sample are high school students of class XI Science PGRI 4 Banjarmasin which consists of class XI IPA 1 as the control class (n = 27) and class 2 as class XI Science experiments (n = 25). Data collection techniques and the value of using student response test and questionnaire techniques. Statistical analysis using ANOVA test path. The results showed that (1) the formation of students' mental models after using blended learning on material solubility and solubility product for the better, (2) learning outcomes between students who learn the material solubility and solubility product using high Lebing blended learning compared with students who learn the material solubility and solubility product using conventional learning, (3) blended learning received a positive response from the students of class XI Science 2 SMA PGRI 4 Banjarmasin on material solubility and solubility product.Keywords: blended learning, mental model, learning outcomes, solubility and solubility product.